Late Pleistocene synchronous caldera-forming eruptions in north and south of Japan: paleomagnetic and tephrochronological evidence from the Kutcharo II/III and Aso-4 tephras - Shohei Shibata; Takeshi Hasegawa; Akihiro Tanimoto; Nobutatsu Mochizuki; Makoto Okada (Earth, Planets and Space)
Abstract We conducted paleomagnetic analysis of two late Pleistocene caldera-forming eruption deposits, the Aso-4 tephra from the Aso caldera in Kyushu and Kp II/III deposits from the Kutcharo caldera in Hokkaido Japan, to constrain the time scales of the successive tephra layers and evaluate their chronological relationships. Aso-4 tephra covers most of the Japanese archipelago and is known as a representative, late Pleistocene time marker. Kp II/III deposits are distributed in eastern Hokkaido and subdivided into three subunits (Kp III, Kp III -ash, and Kp II in ascending order). We investigated the detailed stratigraphy of Aso-4 tephra and Kp II/III deposits. Kp II/III deposits directly overlie Aso-4 tephra at the observed outcrop, while a thin (< 1 cm) brown weathered ash layer recognized between Kp III-ash and Kp II indicates an eruption hiatus. Oriented cube samples were collected from Aso-4 tephra and Kp II/III deposits and were subjected to thermal demagnetization experiments to determine their characteristic remanent magnetization (ChRM). The mean ChRM directions for Kp III, Kp III-ash, and Kp II are distinguishable at the 95% confidence interval (α95). Based on the angular difference in ChRM directions and the maximum rate of change observed for the archaeomagnetic secular variation curve in Japan, we suggest that the time gaps between Kp III and Kp III -ash was at least 71 ± 34 years and that between Kp III -ash and Kp II was at least155 ± 28 years. Mean ChRM direction of the Aso-4 tephra was also well determined (α95 = 3.0°) and shows good agreement with the published data. Mean ChRM direction of the Aso-4 tephra is indistinguishable from that of the Kp III which directly overlies Aso-4 tephra. These results indicate that both caldera-forming eruptions of Kp III in Hokkaido and Aso-4 in Kyushu occurred only within a few decades. They can be considered to be an example of “synchronous caldera-forming eruptions” where they are located > 1,500 km apart. Graphical Abstract